Accreditation in police agencies: Does external quality assurance reduce citizen complaints?. (March 2017) - Hougland, Steven; Wolf, Ross
Accreditation suggests an organisation has met standards of quality through extensive self-study and external review. This study examines the influence of Commission on Accreditation for Law Enforcement Agencies (CALEA) accreditation on citizen complaints. We identified the accredited status of the agencies included in the 2007 LEMAS report as CALEA-accredited or non-accredited resulting in a final sample size for this study of 628 agencies (CALEA accredited = 314, non-accredited = 314). Findings suggest that no difference exists between CALEA-accredited agencies and non-accredited agencies in: (1) the total number of complaints received; (2) the number of sustained citizen complaints.